Eksistensi Institusi Pendidikan dalam Pembangunan dan Perubahan Daerah - Sri Kunarsih; Tampilen Tampilen (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
Regional autonomy gives areas the power to choose their own policies and development paths, including education. To acquire a true picture of area realities, regional independence is required. Large-scale exploitation has resulted in the neglect of regional education development. As a result, there is a natural resource and human resource imbalance in the regions. Educational institutions have an important part in the development of people's minds and creativity. The goal is to enhance education's role in promoting higher-quality change. This research takes a qualitative approach while doing descriptive research. This research tries to provide an overview by presenting a profile (issue) or an outline of the stages to answer questions like who, when, where, and how.